paPowerHouse ... the Zimbabwean immigrant enclave - Magodo, Tina S. (My University, 2012)
In looking more closely at immigrant patterns in urban settings, it appears that safety through anonymity or “invisibility” has primarily been an immediate, limited goal, existing alongside a more persistent, broader goal of safety through visibility. There exists a constant tension between hiding, and wanting to create and participate in a collective identity. (Miranne and Young, 2000) A ‘sense of place’, of spatial belonging, a collective spatial identity arises from a defensive position of trying to resist the urban politics and going against exclusionary practices in general, to create an ‘alternative open space’. (Best and Strüver, 2000) Historically, the formation of enclaves was involuntary, with ethnic ‘ghettos’ arising due to housing discrimination preventing ethnic minorities from settling in certain parts of the city. Ethnic enclaves have since harnessed the potential to contribute positively to urban regeneration with studies showing that, even in the modern contemporary metropolis, members of society still ascribe to ethnic identities, organising themselves spatially into “enclaves” within cities. “Imagining their new surroundings through the memories of their homelands was not merely a means to wrap a cloak of familiarity around a new landscape and thereby re-attain an aura of mastery over the land, but also a means to construct identities for their communities...” (Ferguson and Gupta, 1997) An architectural identity is developed by understanding ourselves in relation to our environment, and the political and economic processes through which environments and spaces are created inevitably limit design’s capacity to inform social change, (le Roux, 2009) and so focusing on immigrant enclave formation then becomes a way of understanding the socio-architectural interplay in current processes of urban transformation in Johannesburg’s Inner City